(untitled) (The Review of Diabetic Studies, 2024)
Holistic care in oncology is an integrative approach that addresses the multifaceted nature of cancer, emphasizing the interconnectedness of physical, emotional, social, and spiritual dimensions of patient well-being. This study explores the critical role of nurses in delivering holistic care to cancer patients, focusing on their responsibilities in assessment, personalized care planning, and pain management. The patient- centered philosophy of holistic care necessitates active engagement and communication between nurses and patients, allowing for tailored interventions that align with individual needs and preferences. Utilizing frameworks such as the Bio- Psycho-Social Model, the study highlights how nurses can enhance patient quality of life and treatment adherence through comprehensive assessments that consider psychological and social factors alongside physiological symptoms. The review identifies key strategies and interventions employed by nurses in managing cancer- related pain and symptoms. Effective pain management is central to holistic care, with nurses utilizing both pharmacological and non-pharmacological methods. The study emphasizes the importance of thorough pain assessment and individualized pain management plans, incorporating complementary therapies such as mindfulness and physical therapies to provide comprehensive relief. However, the implementation of holistic nursing care faces significant challenges, including time constraints, inadequate training in holistic practices, and cultural barriers. The fast- paced nature of oncology settings often prioritizes efficiency over comprehensive care, leading to fragmented patient experiences. Furthermore, the lack of education in holistic approaches limits nurses’ ability to effectively address patients’ diverse needs. The study underscores the necessity of integrating holistic care models into nursing curricula and ongoing professional development to equip nurses with the skills needed for effective patient engagement.